Monitoramento da qualidade da água de poços no Calcário Jandaíra e restrições na agricultura irrigada - Alencar, Renato Dantas (Universidade Federal Rural do Semi-Árido, 2007)
The monitoring/evaluation of the irrigation water hydrodynamic characteristics and quality from wells on area of the aquifer of the Jandaira formation limestone base is of great importance for the fruit crops of the Chapada do Apodi. With this objective an evaluation was carried out on the results of 50 complete analyses (ECw, pH and levels of Na+, Ca2+, Mg2+, K+, Cl-, HCO3 - and CO3 2-) of water samples from several localities inserted in the municipalities of Mossoró-RN, Baraúna-RN and Aracati-CE, Northeast Brazil, collected at the end of the rainfall seasons and at the end of the dry seasons of 2005 and 2006. The values of salinity indexes, water composition and obstruction risk indexes were specific within localities and differentiated among localities, also with variations in function of the period of the year (rainfall season). The dynamic level of wells averaged 18m. Within the same locality the waters varied little with respect to salinity index, however, among the wells of the different localities variations were significant, with absolute values ranging from 1.15 to 4.41 dS m-1. The waters were of low, moderate and severe with regards to restriction due to chloride toxicity, which might affect the yield of sensitive and moderate sensitive crops. The analyses revealed also that the waters have low sodicity and high alkalinity indexes and present low to moderate obstruction risk
Well water quality monitoring in the Jandaíra Formation limestone base and restrictions to irrigated agriculture
Keywords: Water quality; Salinity; Chapada do Apodi; Qualidade de água; Salinidade; Chapada do Apodi; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA